GHG emissions and economic growth : a computable general equilibrium model based analysis for India /: a computable general equilibrium model based analysis for India. ([2015]) - Pal, Barun Deb; Ojha, Vijay Prakash; Pohit, Sanjib; Roy, Joyashree, 1957-
No abstract available